An Efficient Strategy for Boosting Photogenerated Charge Separation by Using Porphyrins as Interfacial Charge Mediators. (11th October 2019) - Ning, Xingming; Lu, Bingzhang; Zhang, Zhen; Du, Peiyao; Ren, Hongxia; Shan, Duoliang; Chen, Jing; Gao, Yunjing; Lu, Xiaoquan
Abstract: Surface recombination at the photoanode/electrolyte junction seriously impedes photoelectrochemical (PEC) performance. Through coating of photoanodes with oxygen evolution catalysts, the photocurrent can be enhanced; however, current systems for water splitting still suffer from high recombination. We describe herein a novel charge transfer system designed with BiVO4 as a prototype. In this system, porphyrins act as an interfacial‐charge‐transfer mediator, like a volleyball setter, to efficiently suppress surface recombination through higher hole‐transfer kinetics rather than as a traditional photosensitizer. Furthermore, we found that the introduction of a "setter" can ensure a long lifetime of charge carriers at the photoanode/electrolyte interface. This simple interface charge‐modulation system exhibits increased photocurrent density from 0.68 to 4.75 mA cm −2 and provides a promising design strategy for efficient photogenerated charge separation to improve PEC performance. Abstract : Ein neues Spiel : Porphyrine wurden als Grenzflächen‐Charge‐Transfer‐Mediator, wie ein „Volleyball‐Setter", identifiziert. Sie unterdrücken die Rekombination von Oberflächenladungen aufgrund höherer Lochtransferkinetik und nicht wie herkömmliche Photosensibilisatoren (siehe Bild). Die Einführung eines „Setters" sorgte für eine lange Lebensdauer der Ladungsträger an der Photoanoden‐Elektrolyt‐Grenzfläche und führte zu einer erhöhten Photostromdichte.